The wedding night - Krentz, Jayne Ann (Ontario : Mira, 1991)
After her marriage to Owen Sutherland, a union she hopes will end the rivalry between their families, Angie Townsend finds her honeymoon shattered by a mysterious caller who informs her that her marriage is nothing more than a clever corporate raid devised by her new husband.
Keywords: Marriage -- Fiction; Suspense fiction